Peningkatan Perekonomian Usaha Kecil Melalui Produk Inovatif dan Kreatif - Kusumawardhani, Nuruni Ika; Sishadiyati, Sishadiyati; Adiawaty, Mei Retno (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The city of Surabaya has a huge regional potential in improving regional economies. Gunung Anyar Tambak area is one of the areas that has enormous natural potential that can be developed as a product that has a selling value that can increase the income of the surrounding community. This study aims to provide an overview of the potential of MSMEs in the city of Surabaya. The method used in this study uses descriptive descriptive method by using SWOT analysis to side with the weaknesses, threats, opportunities and challenges that exist in the processing of natural resources to increase income. With the large number of Payus and Mangrove Fish (Bogem) which are widely available in Gunung Anyar Tambak region, it is expected that the research carried out in the processing of Creative and Innovative products can increase the income of small business actors by looking at or improving market areas, market strategies, packaging forms and opportunities. existingbusiness.